The effect of annealing on the structural, optical, electrical and photoelectric properties of ZnO/NiO heterostructures - M. Yermakov; R. Pshenychnyi; A. Opanasyuk; Yu. Gnatenko; P. Bukivskij; A. Bukivskii; O. Кlymov; V. Muñoz-Sanjosé; R. Gamernyk (Applied Surface Science Advances)
In this study, n-ZnO/p-NiO heterostructures on glass substrates with an indium tin oxide (ITO) covering were obtained by using the spray pyrolysis methodology. In order to act on the structural and local compositional defects, the samples were annealed under vacuum in the temperature range of Ta = (300 – 500) °C in steps of ΔT = 50 °C. X-ray diffraction results indicate the presence of only the hexagonal ZnO and cubic NiO phases in the studied samples, which was confirmed by Raman spectroscopy. Low-temperature photoluminescence (PL), as well as absorption and photoconductivity, were studied to establish the optical properties, the nature of electronic optical transitions, the energy level position of the different defects present in the samples, and the effect of temperature annealing on these properties The band gap of the compounds was determined using the Tauc approximation and the first derivative of the absorption coefficient. Likewise, the current-voltage characteristics of the n-ZnO/p-NiO heterostructures and their diode character, were analyzed.